Assessment on the marketing strategies of corn farmers in selected municipalities of Agusan Del Sur - Duzal, Nice E.; Marzo, Fernando L., Jr. (2007)
This study was conducted in three municipalities of Agusan del Sur: Trento, Sta. Josefa, and Veruela from January to February 2007 to assess the marketing strategies of corn farmers in these selected areas. Descriptive research was used through the aid of questionnaires given to the respondents or corn farmers. The results of the study showed that majority of the respondents engaged in corn farming were from 41 to 50 years old, males, and married. In terms of educational attainment, most were elementary graduates; Cebuanos, and Catholic. They obtained their financial source usually fro farm financiers. Many adopted the conventional farming system and harvested with good yields but low net income because of high production inputs. Capital was their usual problem followed by insect infestation, low price, presence of diseases, high production input, unavailability of labor, and flood. Most of the respondents sold their products through traders/middleman.
Keywords: Corn farmers; Corn farmers -- Marketing strategy; Mindanao studies